# Find $\mathrm{k}$ so that $x^{2}+2 x+k$ is a factor of $2 x^{4}+x^{3}-14 x^{2}+5 x+6$. Also, find all the zeroes of the two polynomials.

Given:

$x^{2}+2 x+k$ is a factor of the polynomial $f(x)=2 x^{4}+x^{3}-14 x^{2}+5 x+6$ when divided by $x^{2}+2 x+k$, the remainder is zero.

To do:

We have to find $k$ and find all the zeroes of the two polynomials.
Solution:
Divide $f(x)=2 x^{4}+x^{3}-14 x^{2}+5 x+6$ by $x^{2}+2 x+k$ by using long division
method.

$x^2+2x+k$)$2x^4+x^3-14x^2+5x+6$($2x^2-3x-2(k+4)$

$2x^4+4x^3+2kx^2$

-----------------------------------

$-3x^3-2x^2(k+7)+5x+6$

$-3x^3-6x^2 -3kx$

--------------------------------------------

$-2x^2(k+4)+x(5+3k)+6$

$-2x^2(k+4)-4x(k+4)-2k(k+4)$

-------------------------------------------------

$x(7k+21)+(2k^2+8k+6)$
Remainder $=x(7 k+21)+\left(2 k^{2}+8 k+6\right)$ and Quotient $=2 x^{2}-3 x-2(k+4)$.
If it is a factor then the remainder $=0$
$\Rightarrow x(7 k+21)+2\left(k^{2}+4 k+3\right)=0$ for all $x$.
$\Rightarrow 7 k+21=0$ and $k^{2}+4 k+3=0$
$\Rightarrow 7(k+3)=0$ and $(k+1)(k+3)=0$
$\Rightarrow k+3=0$

$\Rightarrow k=-3$
Substituting the value of $k$ in $x^{2}+2 x+k$, we get,

$x^{2}+2 x-3=(x+3)(x-1)$ as the divisor.

Its zeros are $-3$ and 1.

Therefore, two zeros of $f(x)$ are $-3$ and $1 .$

For $k=-3$, we get,
Quotient $= 2x^{2}-3 x-2=2 x^{2}-4 x+x-2$

$=2 x(x-2)+1(x-2)$

$=(x-2)(2 x+1)$
Divisor $=x^{2}+2 x-3$

$=x^{2}+3 x-x-3$

$=x(x+3)-1(x+3)$

$=(x-1)(x+3)$
Therefore,
$f(x)=$Quotient$\times$Divisor
$\Rightarrow f(x)=2 x^{4}+x^{3}-14 x^{2}+5 x+6$

$=(x-2)(2 x+1)(x-1)(x+3)$
Hence, zeros of $f(x)$ are $2,\frac{-1}{2},1$ and $-3$.

Tutorialspoint

Simply Easy Learning